2019
DOI: 10.1088/1757-899x/701/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonication process on crystallinity and tear strength of thermoplastic starch/cellulose biocomposites

Abstract: The thermoplastic starch (TPS)/cellulose biocomposites were manufactured as green biocomposite films. TPS was produced through plasticization process in which the mixture of starch granule and plasticizers (water and glycerine) went through the stirring and heating process. Cellulose was used as filler and prepared in suspension form through ultrasonication process involving isolation of cellulose in water medium. The ultrasonicated cellulose suspension was added into the TPS matrix to produce TPS/cellulose bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…They may exhibit poor mechanical performance due to severe issues of water sensitivity, environmental stress cracking, and high fragility over time. Their low mechanical properties are a major concern, especially when exposed to hydrolytic and oxidative conditions and elevated temperatures [ 4 , 8 ]. These restrict the use of the TPS packaging films for long-term application as opposed to the petroleum-based plastic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may exhibit poor mechanical performance due to severe issues of water sensitivity, environmental stress cracking, and high fragility over time. Their low mechanical properties are a major concern, especially when exposed to hydrolytic and oxidative conditions and elevated temperatures [ 4 , 8 ]. These restrict the use of the TPS packaging films for long-term application as opposed to the petroleum-based plastic.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, dolomite particles dispersion in the TPS matrix is very important, since it can affect the mechanical properties of the resultant TPS-DOL biocomposite films. Previous research indicated that a good dispersion of filler leads to improvement in the mechanical properties of the TPS composites, such as tensile and tear strength [ 4 , 8 ]. Generally, the pristine dolomite particles exist in agglomerated form.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymer films based on natural and renewable resources are gaining great attention worldwide as packaging materials due to their characteristics of being biodegradable and bio‐renewable. These natural compositions also do not release harsh chemicals to the atmosphere [2,3] …”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Biopolymers like cellulose, chitin and starch have been studied and researched for packaging applications to substitute for synthetic plastics. [1][2][3] Composite materials based on biopolymers are gaining more attraction due to the mechanical performance of these materials which is almost always greater than their neat biopolymer counterparts. Lignocellulosic-based fibers from sisal, ramie and flax are used to replace conventional glass fibers.…”
mentioning
confidence: 99%
“…However, the dissolution process of cellulose is challenging since cellulose are known to be non-soluble in common solvents (water and conventional organic solvents). The insolubility of cellulose is due to the presence or appearance of intra-and intermolecular hydrogen bonding and Van der Waals interaction which closely pack the chains together, and also the partially crystalline structure of cellulose [8,9]. These restraints have motivated further discoveries and investigations for suitable cellulose dissolution methods to facilitate or aid in the use of cellulose, for example, in applications of regenerated cellulose [8,10,11].…”
Section: Introductionmentioning
confidence: 99%